Genetic polymorphism of milk protein and its effect on milk composition traits in - MANDAL, AJOY; KUMAR, D; ROUT, P K; YADAV, N K; ROY, R (The Indian Journal of Animal Sciences, 2011)
The electrophoretic pattern revealed the presence of three (lsI-casein alleles viz. ascCnA, cx.sI-CnE and cx.S1-CnF in the milk samples of Muzaffamagari sheep. The frequency of predominant cx.sI-CnE locus and rare cx.sl-CnF variant in this population was 0.38 and 0.01, respectively, where the frequency of null allele for this locus (ascCnO) was 0.37. All the loci except B-Cn, B-lactoglobulin and a-lactalbumin locus in the population showed the presence of null allele. No polymorphic patterns were observed at cx.s2-’ B- and Kcasein locus in this study. The -lactoglobulin loci showed the presence ofA and B variants on the gel. The cx.-lactalbumin loci revealed the monomorphic form in the population. The study also showed that as I-casein variant had only significant effect on casein content of milk and none of these milk protein variants had significant effect on total protein content of milk in this breed. Â